The underlying mechanism and targeted therapy strategy of miRNAs cross-regulating EMT process through multiple signaling pathways in hepatocellular carcinoma - Chen, Juan; He, Fuguo; Peng, Hong; Guo, Jinjun (Frontiers in Molecular Biosciences, 2024)
The consistent notion holds that hepatocellular carcinoma (HCC) initiation, progression, and clinical treatment failure treatment failure are affected by the accumulation of various genetic and epigenetic alterations. MicroRNAs (miRNAs) play an irreplaceable role in a variety of physiological and pathological states. meanwhile, epithelial-mesenchymal transition (EMT) is a crucial biological process that controls the development of HCC. miRNAs regulate the intermediation state of EMTor mesenchymal-epithelial transition (MTE)thereby regulating HCC progression. Notably, miRNAs regulate key HCC-related molecular pathways, including the Wnt/β-catenin pathway, PTEN/PI3K/AKT pathway, TGF-β pathway, and RAS/MAPK pathway. Therefore, we comprehensively reviewed how miRNAs produce EMT effects by multiple signaling pathways and their potential significance in the pathogenesis and treatment response of HCC. emphasizing their molecular pathways and progression in HCC initiation. Additionally, we also pay attention to regulatory mechanisms that are partially independent of signaling pathways. Finally, we summarize and propose miRNA-targeted therapy and diagnosis and defense strategies forHCC. The identification of the mechanism leading to the activation of EMT programs during HCC disease processes also provides a new protocol for the plasticity of distinct cellular phenotypes and possible therapeutic interventions. Consequently, we summarize the latest progress in this direction, with a promising path for further insight into this fast-moving field.